Screening of phytochemicals and antibacterial activity of marine red alga Portieria hornemannii (Lyngbye) P. C. Silva - Subbiah, Murugesan; Sundaresan, Bhuvaneswari; U.S. Mahadeva, Rao; Vajiravelu, Sivamurugan (A&V Publications, 2017)
The evaluation of phytochemicals and antimicrobial activities of marine red alga Portieria hornemannii against bacterial pathogens have been established in the present investigation. The quantitative phytochemical screening of the methanol extract of P. hornemannii, showed a maximum number of natural products such as tannins, flavonoids, glycosides, phenols, saponins, terpenoids, etc. The antimicrobial activity of methanol extract of P. hornemannii showed the highest inhibition against Staphylococcus aureus (77.77%) and the chloroform extract showed the lowest activity against Pseudomonas aeruginosa by showing (52.63%) as evaluated by disc diffusion method. Our findings provide the evidence that the methanol extract of P. hornemannii possesses the good antimicrobial activity and hence, the alga proves to be an effective therapeutic agent.